1995
DOI: 10.5144/0256-4947.1995.110
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography Detection of Radiolucent Foreign Bodies in Soft Tissue Compared to Computed Tomography Scan

Abstract: Thirty-one patients with suspected radiolucent foreign bodies (wooden splinters) in soft tissues of extremities were investigated by plain radiography, computed tomography (CT) scan and ultrasonography to the area suspected clinically. Ultrasonography detected and localized radiolucent foreign bodies in 18 of the 31 patients, while only 14 were seen on CT scan. Following surgical exploration, the presence of foreign bodies was confirmed in 20 patients; thus, the accuracy of ultrasonography was 90% while that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…After our complete review of these articles and their reference sections and our limited reviews of other databases, we included 17 articles in this metaanalysis (Table 1). All 17 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] reported data for calculation of sensitivity; however, only 13 [23][24][25][26][27][28][29][30][31][32][33][34]36,37 reported data for calculation of specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After our complete review of these articles and their reference sections and our limited reviews of other databases, we included 17 articles in this metaanalysis (Table 1). All 17 studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] reported data for calculation of sensitivity; however, only 13 [23][24][25][26][27][28][29][30][31][32][33][34]36,37 reported data for calculation of specificity.…”
Section: Resultsmentioning
confidence: 99%
“…Including this study, three studies 26,34,36 reported on only lowerextremity injuries, while three 21,24,29 reported on only upper extremity injuries. Two studies 23,34 reported on exclusively wooden foreign bodies, and two 31,33 examined radiolucent or nonradiopaque foreign bodies.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Al-Zahrani et al in a study on 31 patients with suspected radiolucent wood particles in soft tissues, used CT and ultrasound for foreign body detection and results demonstrated that size of foreign body does not influence their diagnosis. 10…”
Section: Foreign Body Sizementioning
confidence: 99%
“…Na literatura, alguns estudos sugerem que a US seja o melhor método para diagnosticar CE 6,13 . Com utilização de cadáveres, CEs de madeira, plástico, metal e vidro foram avaliados, indistintamente, e a sensibilidade e a especificidade variaram de 89% a 94% e de 94% a 99% 14,15 , respectivamente.…”
unclassified
“…Em um relato com 39 pacientes, a TC sugeriu a presença de 14 CEs, enquanto a exploração cirúrgica revelou 20 CEs, resultando em uma sensibilidade de 70%. Contudo, neste mesmo estudo, a US foi superior, com uma sensibilidade de 90% 13 . Em nossa pesquisa, a madeira se apresentou como uma imagem hiperdensa à TC (Figura 1C) e, dentre todas as modalidades de exame, este apresentou os mais altos percentuais de sensibilidade e acurácia.…”
unclassified